1997
DOI: 10.1159/000129505
|View full text |Cite
|
Sign up to set email alerts
|

p53 Overexpression and Prolif erative Activity Do Not Correlate with Lymph Node Metastasis in Early Gastric Cancer

Abstract: We investigated p53 overexpression and the proliferative activity of the primary lesion as well as the clinicopathological features of 75 patients with gastric cancer invading the submucosa (sm cancer), of whom 14 (18.7%) had lymph node metastasis. Among the clinicopathologic features studied, only lymphatic invasion by the primary tumor was related to lymph node metastasis. There was no relationship between immuno-histochemical staining for p53 protein or Ki-67 and lymph node metastasis. The p53-positive rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 0 publications
3
8
1
Order By: Relevance
“…Likewise, the positive association of LBVI with the diVuse histological type in our patient population seems to be in relation with the growth pattern of these gastric carcinomas, in which the tumoral cells exhibit a greater motility and more involvement of tisullar structures. In addition, we found that LBVI is closely related to presence of lymphatic node metastases, as previously reported (Gabbert et al 1991;Dicken et al 2006;Duraker et al 2003;Guadagni et al 1993;Ishigami et al 1999;Kanai et al 1997). Thus, this Wnding suggests that the presence of LBVI can be an indication for a more extensive surgical resection.…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, the positive association of LBVI with the diVuse histological type in our patient population seems to be in relation with the growth pattern of these gastric carcinomas, in which the tumoral cells exhibit a greater motility and more involvement of tisullar structures. In addition, we found that LBVI is closely related to presence of lymphatic node metastases, as previously reported (Gabbert et al 1991;Dicken et al 2006;Duraker et al 2003;Guadagni et al 1993;Ishigami et al 1999;Kanai et al 1997). Thus, this Wnding suggests that the presence of LBVI can be an indication for a more extensive surgical resection.…”
Section: Discussionsupporting
confidence: 89%
“…3,7,15,16 In this study, we showed that lymphatic invasion is closely related to the presence of lymph node metastases, as previously reported. 16 Maehara 15 has shown that gastric cancer with lymphatic invasion has a higher proliferation activity and a greater ability to metastasize to distant organs. Kanai 16 has demonstrated in patients with early gastric cancer that lymphatic invasion correlates better with the pres-…”
Section: Discussionsupporting
confidence: 87%
“…A correlation has been shown between Ki-67 expression and the ability of some gastric cancers to metastasize to lymph nodes [29,30]. In other reports, no relationship was found between Ki-67 expression and lymph node metastasis [31]. The present study showed no significant difference between metastatic group and nonmetastatic group in Ki-67 expression, suggesting that cell proliferative ability of early gastric cancers does not have a direct effect on metastasis.…”
Section: Discussioncontrasting
confidence: 56%